Shared Norms and Nomotrophic Behaviour - Passerini Glazel, Lorenzo (Phenomenology and Mind, 2016)
The paper proposes to construe the “interventions in the lives of others when one thinks that the others’ behaviour is wrong” (Devlin and Gilbert), and the “reactions to disappointment of normative expectations” (Niklas Luhmann) under the notion of “nomotrophic behaviour”, i.e. a behaviour that aims at the maintenance of a norm in the event of its infringement. Subsequently, some of the implications of nomotrophic behaviour at an epistemological level (as a clue for inferring norms from action), and at an ontological level (with respect to the existence of norms) are investigated. The paper then examines a possible norm-generating (nomogenic) effect of “nomotrophic behaviour am Phantasma”, and eventually inscribes the different forms of nomotrophic behaviour in the superordinate category of “meta-normative behaviour”.